The Recess Queen - O'Neill, Alexis, 1949-; Huliska-Beith, Laura (New York : Scholastic Press, 2002)
Mean Jean is the biggest bully on the school playground until a new girl arrives and challenges Jean's status as the Recess Queen.
School Library Journal, March 2002.
Publisher's Weekly, January 2002.
Booklist, March 2002.
Bulletin (Center for Children's books), March 2002.
Kirkus Review, December 2001.
Library Talk, May 2002.
Keywords: Bullying -- Juvenile fiction; Schools -- Juvenile fiction; Bullies -- Fiction; Schools -- Fiction; Bullies -- Fiction; School stories; Bullies -- Fiction; Schools -- Fiction